PENGARUH PERLAKUAN ALKALISASI DAN VARIASI FRAKSI VOLUME KOMPOSIT POLYESTER SERAT BEMBAN (Donax Canniformis) TERHADAP KEKUATAN IMPAK - Akhmad Wahyudi; Akhmad Syarief (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2016)
The Indonesian state is rich in natural resources, the various benefits of natural resources are useful for human survival. Various kinds of plants in Indonesia are useful as technical material.One of the engineering materials is Composite. Composite is a material formed from a combination of two or more matrials that have stronger mechanical properties than the material forming. The composite consists of two parts: a matrix as a binder or a composite protector and a filler as a composite filler. Natural fiber is an alternative filler, and bemban fiber (Donax Canniformis) is one of the many natural fibers grown in the Hulu Sungai Selatan area of South Kalimantan. From the research result, the influence of volume fraction on composite fiber bemban has the most optimum strength that is on variation 60% fiber bemban 40% Polyester with no alkalization that has absorption energy 13.23 joule and the impact price of 0.067 joule / mm².